Electromagnetic Field Analysis and Shielding Method of Underground Variable Frequency Power Cable - Jianwei Zhang; Zhuojing Yang (Advances in Civil Engineering)
The transmission and radiation of underground variable frequency electromagnetic waves will seriously interfere with the operation of the power cable and its surrounding environment. At present, the test methods for power cables basically require the impedance of the test system to match the characteristic impedance of the cable. The defect is that the process of designing and making the impedance matching impedance network is relatively complex and requires high manufacturing accuracy. In order to solve these problems, this paper puts forward the electromagnetic field fast detection formula and electromagnetic field shielding method of underground variable frequency power cable. The research method of this paper is the principle of shielding electromagnetic field materials and the suppression principle of shielding layer for electromagnetic coupling. The function of the two principles is to study the reflection, absorption, and multiple reflection of electromagnetic waves and to study the cut-off frequency of the nonmagnetic shielding layer. These two principles guide the experiment. In this paper, the measurement formula of the shielding performance of mismatched cables is derived through experiments. The results show that the error of the measurement formula is no more than 8 dB. Then, through the experiment of restraining the interference of magnetic materials on the electromagnetic field, it is concluded that the magnetic field shielding performance can reach 20 dB. Then, through the performance test of electromagnetic field shielding materials, the shielding efficiency of metal fiber antiradiation materials is the largest, and the average efficiency reaches 76.4 dB.